An Adaptive Learning Approaches for Postgraduate Students with Mental Health Challenges - Abdullah Asuhaimi, Farhana; Ahmad, Siti Noor; Baharuddin, Helyawati (Malaysian Journal of Information and Communication Technology (MyJICT), 2025)
The use of adaptive learning technologies into higher education has attracted growing interest., particularly in addressing the unique needs of learners with mental health challenges. This bibliometric study investigates the research landscape on adaptive learning approaches for postgraduate students experiencing mental health difficulties. Using data extracted from Scopus, the study maps publication trends, influential authors, key journals, countries, and thematic clusters within this domain. The analysis employs tools such as VOS viewer and Perish software for visualization and knowledge mapping. The results highlight a growing but fragmented body of scholarship, with limited focus on postgraduate-level learners and specific mental health contexts such as depression and anxiety. This study contributes by identifying research gaps, offering insights for future investigation, and emphasizing the need for interdisciplinary collaboration in designing AI-driven adaptive learning systems that support the academic and emotional well-being of postgraduate students.